2019
DOI: 10.1136/acupmed-2018-011738
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of variable durations of pressure release technique on latent myofascial trigger points of the levator scapulae: a double-blinded randomised clinical trial

Abstract: Objective: Latent myofascial trigger points (MTrPs) of the levator scapulae have a high prevalence and may influenceconditions of the neck and shoulder. The pressure release technique is one of the most recommended manual therapy techniques. The aim of this study was to determine the effect of varying durations of the pressure release technique application on latent MTrPs of the levator scapulae. Methods: In a three-arm (1:1:1 ratio), double-blinded, parallel, randomised clinical trial, 60 healthy university s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…The explanation about the lack of change in the diagnosis after the muscle manipulation is based on the time that is required to manage the inflammatory process. The findings of this study concur with the results of Calixtre et al 15 In that systematic review, they concluded that OMT (release and myofascial massage) would relieve pain and increase pain threshold under pressure in subjects with signs and symptoms of temporomandibular disorders. However, the authors indicated that the results may vary depending on the therapeutic technique used.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The explanation about the lack of change in the diagnosis after the muscle manipulation is based on the time that is required to manage the inflammatory process. The findings of this study concur with the results of Calixtre et al 15 In that systematic review, they concluded that OMT (release and myofascial massage) would relieve pain and increase pain threshold under pressure in subjects with signs and symptoms of temporomandibular disorders. However, the authors indicated that the results may vary depending on the therapeutic technique used.…”
Section: Discussionsupporting
confidence: 92%
“…27,28 It is possible that, in patients with MFP, the muscles are affected by a decrease in the blood flow due to a vasoconstriction produced after an increase of activity. 15 Under this situation, nutrients and metabolites would be altered and inflammatory mediators could sensitize the nociceptors and provoke pain. 29,30 Moreover, the trigger points will cause referred pain, movement difficulties, fatigue, and other muscles dysfunctions.…”
Section: Omtmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of sampling utilized was the lottery method. Sample size was calculated statistically based on the previous research studies 15 . The inclusion criteria were patients with active MTrP's over the trapezius muscle, both male and female subjects between the age group of 18-24 years whereas the exclusion criteria were patients with more than one active MTrP, those having other co-morbidities like diabetes, hypertension etc.…”
Section: Methodsmentioning
confidence: 99%
“…14 On the other hand, the positional release technique is suggested to be a better treatment option than ischemic compression because its lower compression and thus inturns allows adequate oxygenation to the muscle. 15 Although conventional PRT is known to be effective when given in combination, low pressure and a long duration, or high compression and short duration, may be more effective for immediate pain reduction. 16 There are evidences of numerous research studies which have investigated the efficacy of PRT as well as ICT on MTrP's.…”
Section: Introductionmentioning
confidence: 99%